2012
DOI: 10.1016/j.socscimed.2011.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unequal employment status on workers’ health: Results from a Japanese national survey

Abstract: This study assesses the possibility of a period effect on Japanese workers' health and its association with historical changes in the work environment. We used multi-year national cross-sectional surveys, the Comprehensive Survey of Living Conditions for 2001, 2004, and 2007, and estimated the period effect on the health of employed workers aged 18-65 years. The prevalence of ill-health indicators (poor self-rated health status, subjective symptoms, and the number of respondents receiving consultations from me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…Workers unsatisfied with their contract terms [16] report lower self-rated health and the insecurity due to contract uncertainty is such that transitions from unemployment to fixed-term employment does not increase the perceived health condition, at least in the short run [17]. In addition, self-rated health is sensitive to economic deprivation due to intermittent spells of employment, so that workers are unsatisfied with their material reward [18], and to the lack of benefits provided by a stronger employment protection [19]. Recently, cross-country analyses have also been carried out with the purpose of highlighting differences in the link between insecurity and poor health within Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Workers unsatisfied with their contract terms [16] report lower self-rated health and the insecurity due to contract uncertainty is such that transitions from unemployment to fixed-term employment does not increase the perceived health condition, at least in the short run [17]. In addition, self-rated health is sensitive to economic deprivation due to intermittent spells of employment, so that workers are unsatisfied with their material reward [18], and to the lack of benefits provided by a stronger employment protection [19]. Recently, cross-country analyses have also been carried out with the purpose of highlighting differences in the link between insecurity and poor health within Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we calculated the relative poverty rate by employment contract and household structure based on the definition described above. In line with previous studies based on data from the CSLC 29,35) , we did not adjust the sample weights because the CSLC is not strictly based on probabilistic sampling and the sample weights the government offers are only useful for expanding the estimated totals of the number of households or household members from a sample to the subnational level 26) . All analyses were conducted using R version 2.12.2 36) .…”
Section: Discussionmentioning
confidence: 99%
“…selected from five possible response options ("excellent", "very good", "good", "fair" or "poor"). Following previous studies based on data from the CSLC 29) , we classified these responses into the following two categories: "fair/ poor" or "excellent/very good/good". Previous studies have shown SRH to be a validated indicator of overall health and to be an independent predictor of overall mortality 30) .…”
Section: Variablesmentioning
confidence: 99%
“…An a posteriori hypothesis suggested that the increase in precarious non-regular work may have been the main cause of the deterioration in workers' health. 34 The working conditions of nonregular workers are known to be very poor compared with those of regular workers in terms of salary and welfare systems, 26 and opportunities to be a full-time regular worker are very limited. Indeed, it is often the case that only new graduates became regular workers.…”
Section: Discussionmentioning
confidence: 99%